International aid management in Afghanistan's health sector from the perspective of national and international managers - Noorullah Rashed; Hamidreza Shabanikiya; Leili Alizamani; Jamshid Jamali; Fatemeh Kokabisaghi (BMC, 2024)
Abstract Purpose The primary purpose of international aid is to promote economic and social development around the world. International aid plays an important role in Afghanistan's healthcare system. The purpose of this study is to investigate international aid management in Afghanistan's health sector from the perspectives of national and international managers in 2022 and to provide recommendations for the improvement. Design/methodology/approach The study has a cross-sectional design. The study participants were chosen by random sampling. The sample size was determined based on Yaman's formula at 110. The data collection tool was the questionnaire provided by International Health Partnership and Related Initiatives. The data were analyzed in two descriptive (mean and percentage) and analytical formats. Independent t-test, Mann-Whitney, Kolmogorov-Smirnov tests and Variance analysis were used to examine the relationships between demographic variables and the scores of each dimension. Findings The average scores given to different dimensions of aid management were as following: 1) the donners' support of the national health strategy: 48/68 ± 16.14 (49%), 2) the predictable financing: 50/23 ± 16.02 (50%), 3) foreign aid on budget: 55/39 ± 20.15 (55%), 4) strengthening public financial management system: 38/35 ± 19.06 (38%), 5) strengthening the supply and procurement system: 40.97 ± 19.55 (41%), 6) mutual accountability: 46.50 ± 19.26 (46%), 7) technical support and training: 50.24 ± 17.33 (50%), 8) civil society involvement: 35.24 ± 18.61(35%), 9) private sector participation: 36 ± 17.55 (36%), and in total the average score was 44.52 ± 13.27 (44%). The difference between the scores given by two groups of managers was not significant. No meaningful relationship was observed between the total score and any of the demographic variables, but there was a weak relationship between work and management experience and total score. The correlation coefficient showed a statistically significant relationship between the different dimensions of the questionnaire. To sum up, the performance in all dimensions of aid management hardly reached 50%. Donors' support for the national health strategy was not adequate. There were challenges in evidence-based decision-making, developing national health strategies, control and evaluation, the allocation of resources and use of procurement system. The priorities of donors and government were not always similar and mutual responsibility was lacking. Technical assistance and supporting multilateral cooperation are necessary. Originality/value Most studies on foreign aid focused on its effects on economic growth, poverty and investment and not aid management processes. Without proper aid management, parts of resources are wasted and aims of aid programs cannot be achieved. This study investigates aid management in a developing country from the perspectives of two main stakeholders, international and national managers. Research limitations and implications Data collection coincided with the change of government in Afghanistan. The situation might be different now. Still, this study provides areas for the improvement of aid management in the studied country. Future studies can build upon the findings of this research and conduct in-depth exploration of areas of aid effectiveness and designing detailed programs of improvement. Practical implications Instructions of the Paris Declaration on Aid Effectiveness need to be followed. Particularly, civil society involvement and private sector participation should receive attention. A joint plan for improvement and collaboration of different stakeholders is needed.